Pesticides - Charbonnier, Edwige; Ronceux , Aïcha; Carpentier , Anne-Sophie; Soubelet , Hélène; Barriuso , Enrique (éditions Quae, 2015)
Pesticides are today the subject of considerable environmental issues. This work presents the outcome of fifteen years of research financed by the French Ministry of Ecology on the reduction in environmental risks from using pesticides. It emphasises especially the transfer of results to support public decisions.